Administration of Single-Dose Antibiotic Does Not Decrease Oronasal Fistula Rates After Primary Palatoplasty. (January 2022) - Mamidi, Ishwarya Shradha; Mantilla-Rivas, Esperanza; Ichiuji, Brynne A.; Rana, Md Sohel; Ramirez, Karen I.; Stein, Jason R.; Aivaz, Marudeen; Manrique, Monica; McGrath, Jennifer; Rogers, Gary F.; Oh, Albert K.
Objective: Oronasal fistula (ONF) is a known complication after primary palatoplasty (PP). Studies investigating the effect of perioperative antibiotics on fistula rates after PP are limited by inadequate sample size or reliance on self-reporting through national databases. In this study, the authors evaluated the association between single-dose perioperative antibiotics and postoperative fistula rates after PP at a single institution. Design: A retrospective study. Participants: Children younger than 2 years who underwent PP from April 2009 to September 2019 were included. Interventions: Patients were divided into 2 categories: Group 1 received a single intraoperative dose of IV antibiotic, while group 2 did not. Main Outcome Measure(s): Outcome measures included ONF formation, length of stay (LOS), and 30-day readmission rates. Multivariable firth logistic regression, quantile regression, and χ 2 tests were performed. Results: Of the 424 patients, 215 and 209 patients were in groups 1 and 2, respectively. The overall ONF rate was 1.9% among all patients. Patients in group 1 experienced an ONF rate of 3.3%, while patients in group 2 had an ONF rate of 0.5%. After correcting for confounding variables, the difference in ONF rates was not statistically different ( P = .68). Median LOS was 35.7 hours and 35.5 hours ( P = .17), while the rate of readmission within 30 days was 4.7% and 2.4% for group 1 and 2, respectively ( P = .96). Conclusions: Administration of a single-dose perioperative antibiotic did not decrease fistula formation after PP, nor did it affect the patient's LOS or 30-day readmission rate.